2018
DOI: 10.1029/2018gc007562
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Transition Layer Beneath the Earth's Inner Core Boundary From Observations of Antipodal PKIKP and PKIIKP Waves

Abstract: Standard Earth models assume a simple uniform inner core boundary (ICB) separating the liquid iron outer core from the solid iron inner core. Metallurgical and geodynamic experiments, however, predict lateral variations along this boundary originating from thermochemical and geodynamic instabilities during solidification. We search for evidence of this lateral heterogeneity by exploiting the sensitivity of antipodal PKIIKP waveforms to the shear wave velocity structure of the uppermost inner core beneath their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 133 publications
0
6
0
2
Order By: Relevance
“…Our model has the virtue of not requiring any new properties of the inner or outer core, simply the evolution of a known solid property, the inner core's anisotropy, as the core crystallizes. Similarly, lateral changes in the ICB's properties (Attanayake et al, 2018;Krasnoshchekov et al, 2005) or topography (Cao et al, 2007;de Silva et al, 2017) may also modulate PKiKP amplitudes, but anisotropy's first-order effect on amplitudes suggests that a parsimonous approach would first attribute amplitude changes to changes in anisotropy to before invoking other effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our model has the virtue of not requiring any new properties of the inner or outer core, simply the evolution of a known solid property, the inner core's anisotropy, as the core crystallizes. Similarly, lateral changes in the ICB's properties (Attanayake et al, 2018;Krasnoshchekov et al, 2005) or topography (Cao et al, 2007;de Silva et al, 2017) may also modulate PKiKP amplitudes, but anisotropy's first-order effect on amplitudes suggests that a parsimonous approach would first attribute amplitude changes to changes in anisotropy to before invoking other effects.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported evidence for topography or other types of lateral heterogeneity at the ICB (e.g., Attanayake et al., 2018; Blom et al., 2015; Cao et al., 2007; Dai et al., 2012; Koper & Dombrovskaya, 2005; Krasnoshchekov et al., 2005; Song & Dai, 2008; Stroujkova & Cormier, 2004; Tanaka & Tkalčić, 2015; Tian & Wen, 2017; Waszek & Deuss, 2015; Wen, 2006; Zou et al., 2008), raising the possibility that pre‐critical PKiKP coda waves may be generated at the ICB as opposed to within the volume of the inner core. For instance, Poupinet and Kennett (2004) proposed that PKiKP coda waves recorded at distances less than 45° at the Warramunga array in Australia were created by complex reverberation or resonance effects at the ICB.…”
Section: On the Origin Of Anomalously Long Pkikp Coda Waves At Pre‐cr...mentioning
confidence: 99%
“…(5) We determined the PKIIKP time window, using a 10-s time window centered on the theoretical arrival time of PKIIKP (Figure 3a). The 10-s threshold was chosen to reduce the interference of the neighboring phase PKP-C diff when picking the PKIIKP phase (Attanayake et al, 2018). The peak amplitude near the beginning portion of the time window was selected as the determinant of PKIIKP arrival time.…”
Section: Datamentioning
confidence: 99%